2022
DOI: 10.1017/s0033291722001507
|View full text |Cite
|
Sign up to set email alerts
|

Staging of unipolar depression: systematic review and discussion of clinical implications

Abstract: Staging has been increasingly used in unipolar depression since its introduction in the nineties. Several models are available, but their differential features and implications are not completely clear. We systematically reviewed: (a) staging models of longitudinal development of unipolar depression; (b) staging models of treatment-resistant unipolar depression; (c) their applications. MEDLINE, PsycINFO, EMBASE, and Web of Science were examined according to PRISMA guidelines from inception to December 2021. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…The model for unipolar depression included 5 stages: prodromal phase, acute major depressive episode, residual phase, dysthymia/recurrent major depression, and chronic major depressive episode [34]. This classification retained its basic structure in subsequent proposals [35]. Staging may be based on the longitudinal development of disorders, its progression in terms of severity and complications, or response to treatment.…”
Section: Staging and The Longitudinal Development Of Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model for unipolar depression included 5 stages: prodromal phase, acute major depressive episode, residual phase, dysthymia/recurrent major depression, and chronic major depressive episode [34]. This classification retained its basic structure in subsequent proposals [35]. Staging may be based on the longitudinal development of disorders, its progression in terms of severity and complications, or response to treatment.…”
Section: Staging and The Longitudinal Development Of Symptomsmentioning
confidence: 99%
“…For instance, according to the DSM-5 cross-sectional perspective [14], certain symptoms may not reach the diagnostic threshold of a disorder and be discarded as of minor value. Yet, with staging the same symptoms can be interpreted as residual after a course of treatment and may constitute a considerable risk for relapse [35]. Staging is thus uniquely geared to identifying individual trajectories.…”
Section: Staging and The Longitudinal Development Of Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only very recently, Cosci and Fava [35] published an updated systematic review of studies concerned with staging models in adult patients with unipolar depression, including an adapted version of their 2013 [17] model of staging unipolar depression: prodromal phase with either nonspecific symptoms or subthreshold depressive symptoms (stage 1); first major depressive episode (stage 2); residual phase, including nonspecific symptoms, residual depressive symptoms, and dysthymia (stage 3); recurrent or double depression (stage 4); and chronic major depressive episode (stage 5). Interestingly, the great majority of studies found in Cosci and Fava’s [35] 2022 review described models of staging treatment resistance, while only a minority dealt with staging models of longitudinal development of symptoms. Also, an additional staging model of tolerance to, and side effects of, antidepressant drugs was proposed by Cosci and Chouinard [36].…”
Section: Staging Treatment Resistancementioning
confidence: 99%
“…In addition, the NICE guidelines do not mention that withdrawal symptomatology may be associated with loss of treatment efficacy despite adequate adherence to the antidepressant treatment and lack of response to a previously effective antidepressant treatment when it was restarted, which is part of treatment resistance [21]. These clinical manifestations can deeply influence the individual trajectories of development of a mental disorder, representing the trigger to move to a different, and more severe or chronic, stage of the same illness [22]. In brief, clinicians must manage what is not mentioned in guidelines; most importantly when a drug is started, clinicians should know what may happen at dose decrease and drug discontinuation.…”
mentioning
confidence: 99%